PARASITIC CONTAMINATION: PREVALENCE AND LOAD IN RELATION TO WATER QUALITY OF AHI RIVER IN UMUAHIA, ABIA STATE - Anyanwu, Emeka Donald; Irole-Eze, Ozioma Prisca; Ihemanma, Chioma Ada; Hilary, Ananda Chisom; Stephen, Amarachi Grace (FUDMA Journal of Sciences, 2026)
Water is an essential resource needed by humans for most of their activities. However, human activities have resulted in the contamination of surface water bodies with chemical and biological agents. Prevalence, parasitic load and some physicochemical parameters of a rural water source in Ohiya Community, Umuahia, Abia State was assessed. The parameters were determined with standard analytical procedures. Grab and composite filtration methods were used for parasite sample collection and sedimentation method for the analysis. Some pH (33.3%) and dissolved oxygen (94.4%) values did not conform to regulatory limits out of nine (9) parameters evaluated. The study recorded 8 parasites (including helminths and protozoa) of public health significance. The overall parasitic contamination prevalence was 75.0%, 77.8% (grab method) and 72.2% (composite filtration method). The most prevalent parasite was Entamoeba coli (41.7%) and the least was Balantidium coli (2.8%). Station 2 had the maximum prevalence (91.7%) and parasitic load (84) while station 3 had the least prevalence (58.3%) and load (22). May and June 2023 had the maximum prevalence (100%) while the maximum parasitic load (74) was recorded in May 2023. On the other hand, July and August 2023 had the minimum prevalence (50.0%) while the minimum parasitic load (6) was recorded in July 2023. The composition, prevalence and parasitic load were highly influenced by physicochemical parameters, sampling method, anthropogenic-related stressors and rainfall. Based on the findings of this study, treatment of the water is required before usage. Solid wastes disposal and discharge of effluents around the river should be prohibited.